2014
DOI: 10.1124/mol.114.092684
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of CD20 Monoclonal Antibody–Mediated Tumor Cell Killing Mechanisms: Rational Design of Dosing Strategies

Abstract: Since approval of rituximab for treatment of B cell non-Hodgkin lymphoma, development of monoclonal antibodies (mAbs) for cancer treatment and elucidation of their cytotoxic mechanisms have been subject to intense investigations. Compelling evidence indicates that rituximab and another CD20 mAb, ofatumumab, must use the body's cellular and humoral immune effector functions to kill malignant cells. Other U.S. Food and Drug Administration-approved mAbs, including obinutuzumab, cetuximab, and trastuzumab, require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 77 publications
(105 reference statements)
3
35
0
Order By: Relevance
“…52,54,64 We suggest that modified dosing schedules with these, or other mAbs now in development, have the potential to address the issue of trogocytosis, and thus enhance mAb efficacy, and may provide a revolutionary paradigm shift in the treatment of cancer patients with certain immunotherapeutic mAbs. 53 In contrast, the results of a doseescalation trial for CLL indicated a higher level of efficacy for single agent RTX at (higher) weekly doses of 2250 mg/m, 2,65 although all remissions were partial. It is possible that the very high RTX doses in part blocked Fcg receptors 13,19,21,22 and thus had the net effect of decreasing trogocytosis.…”
Section: Alternative Dosing Paradigmsmentioning
confidence: 96%
See 1 more Smart Citation
“…52,54,64 We suggest that modified dosing schedules with these, or other mAbs now in development, have the potential to address the issue of trogocytosis, and thus enhance mAb efficacy, and may provide a revolutionary paradigm shift in the treatment of cancer patients with certain immunotherapeutic mAbs. 53 In contrast, the results of a doseescalation trial for CLL indicated a higher level of efficacy for single agent RTX at (higher) weekly doses of 2250 mg/m, 2,65 although all remissions were partial. It is possible that the very high RTX doses in part blocked Fcg receptors 13,19,21,22 and thus had the net effect of decreasing trogocytosis.…”
Section: Alternative Dosing Paradigmsmentioning
confidence: 96%
“…8,26 Additional reports indicate that other mAb-promoted cytotoxic effector functions, including NK-cell-mediated antibody-dependent cellular cytotoxicity and phagocytosis by macrophages, can also be exhausted after CD20 mAb infusion under conditions of high CLL cell burdens. [50][51][52][53] Thus, trogocytosis takes over as an alternative reaction after the body's normal cytotoxic effector functions are exhausted. We have extended and generalized these studies to include ofatumumab (OFA), a next generation CD20 mAb.…”
Section: Modern Times and Mechanismsmentioning
confidence: 99%
“…Upon binding to target cell, anti-CD20 mAbs are expected to activate the classical complement pathway but it is not clear, which effector arm of the complement system contribute to the therapeutic effect (Okroj et al, 2013b). Also, it is not always the case that complement attack on tumor cells will proceed to the lytic stage, as malignant B cells may shed CD20-mAb complexes (Taylor and Lindorfer, 2014) and widely express the complement inhibitors CD46 and CD55 preventing C5 cleavage (Okroj et al, 2013a). Two samples were taken from each patient: one just before and the second immediately after CD20 mAb infusion.…”
Section: Measurement Of Soluble Markers Of Complement Activation In Pmentioning
confidence: 99%
“…Anti CD20 mAbs currently indicated for the treatment of chronic lymphocytic leukemia bind at different CD20 epitopes. function saturation and reduce trogocytosis [10,11]. This approach may have general applicability to other mAbs that use immune effector functions, and could be formulated into a subcutaneous treatment strategy that would be more accessible and possibly more efficacious for patients [10,11].…”
Section: Ofatumumabmentioning
confidence: 96%